2011
DOI: 10.5005/jcd-1-2-40
|View full text |Cite
|
Sign up to set email alerts
|

Management of non vital maxillary central incisors with open apex using Mineral Trioxide Aggregate apical plugs – Case report

Abstract: Management of non vital maxillary central incisors with open apex Management of non vital maxillary central incisors with open apex Management of non vital maxillary central incisors with open apex Management of non vital maxillary central incisors with open apex AbstractThe case report describes the treatment of maxillary central incisors with open apex, due to apical root resorption, as a consequence of trauma experienced three years earlier. Open apices pose a challenge during endodontic treatment. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…3 It has shown considerable success as an artificial apical barrier and has become the material of choice for single-visit apexification. 4,5 In long-term clinical outcome studies of CaOH and MTA apexifi cation, MTA showed similar healing of periapical lesions in shorter treatment durations. 6 The internal matrix acts as a layer that forms a barrier for limiting the extension of repair material 1 such as MTA.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has shown considerable success as an artificial apical barrier and has become the material of choice for single-visit apexification. 4,5 In long-term clinical outcome studies of CaOH and MTA apexifi cation, MTA showed similar healing of periapical lesions in shorter treatment durations. 6 The internal matrix acts as a layer that forms a barrier for limiting the extension of repair material 1 such as MTA.…”
Section: Introductionmentioning
confidence: 99%